Forskjellige Forhold vedrørende Kvægexporten til England. Diskussion, d. 29. Marts 1876. - Green, J. S. (Tidsskrift for Landøkonomi, 2018)
Forskjellige Forhold vedrørende Kvægexporten til England. Diskussion, d. 29. Marts 1876.